2005
DOI: 10.1161/01.cir.0000162483.51132.25
|View full text |Cite|
|
Sign up to set email alerts
|

Arterial Hemodynamics in Patients After Kawasaki Disease

Abstract: Background-Histopathological findings in the acute stage of Kawasaki disease (KD) indicate widespread vascular inflammation that involves not only coronary arteries but also systemic arteries. This may cause changes in systemic arterial wall properties after KD, which could have adverse effects on arterial hemodynamics (an important predictor of cardiovascular morbidity and mortality). Methods and Results-Systemic arterial hemodynamics were investigated by measuring aortic input impedance during cardiac cathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…While such discrete reflections do occur and may have substantial magnitude locally, the arrangement of the arterial tree markedly attenuates the backward travel of waves such that a limited amount of reflection is evident in the proximal aorta once the arterial reservoir is accounted for (30, 33, 35). In this regard, our observations are consistent with a previous invasive study of healthy children (27) and other studies in anesthetized dogs (16). …”
Section: Discussionsupporting
confidence: 93%
“…While such discrete reflections do occur and may have substantial magnitude locally, the arrangement of the arterial tree markedly attenuates the backward travel of waves such that a limited amount of reflection is evident in the proximal aorta once the arterial reservoir is accounted for (30, 33, 35). In this regard, our observations are consistent with a previous invasive study of healthy children (27) and other studies in anesthetized dogs (16). …”
Section: Discussionsupporting
confidence: 93%
“…The pulmonary vascular bed also has many bifurcations with caliber changes. In this type of system, blood flow and pressure waves produce reflections at the site of a bifurcation or vessel caliber change [1,2]. Therefore, the measured pressure or flow we observe is the sum of forward and reflected waves, and thus augmentation of reflected waves causes significant pressure elevation (Fig.…”
Section: Physiologic Components Of Pulmonary Circulationmentioning
confidence: 90%
“…Senzaki et al23) reported that there is an a characteristic increase in impedence, a decrease in total peripheral arterial compliance, and an increase arterial wave reflexion, regardless of the presence of coronary artery lesions in patients with KD. It has also been reported that there is stiffness of the aorta, carotid artery, and brachio-radial artery in the late stage in children who have a history of KD 24-26).…”
Section: Discussionmentioning
confidence: 99%
“…Even in patients who have no coronary lesions, such findings as a pre-atherosclerotic lipid profile,26) endothelial function,23) systemic arterial stiffness24) and increased cIMT are observed.…”
Section: Discussionmentioning
confidence: 99%